Overview of Critical Parameters for the Design and Execution of a High‐Throughput Screen for Allosteric Ligands. Issue 1 (16th September 2016) - Alt, Andrew
Abstract: Allosteric ligands modulate the activity of receptor targets by binding to sites that are distinct from the orthosteric (native agonist) binding site. Allosteric modulators have potential therapeutic advantages over orthosteric agonists and antagonists, including improved selectivity, and maintenance of the spatial and temporal fidelity of native signaling patterns. The identification of allosteric ligands presents unique challenges because of the requirement for screening in the presence of an orthosteric agonist, the small signal window that is produced by many allosteric modulators, the proclivity of allosteric modulators to exhibit activity switching within a chemotype (e.g., one compound may be a positive allosteric modulator while a close analog is a negative allosteric modulator), and probe dependence (differential interactions with different orthosteric agonists). Described in this unit are emerging strategies for the identification of allosteric ligands by high‐throughput screening (HTS), including the use of multiple‐add/multiple‐read HTS assays and tool molecule‐based screening formats. © 2016 by John Wiley & Sons, Inc.